Centromere protein J is overexpressed in human glioblastoma and promotes cell proliferation and migration. Issue 6 (25th July 2022) - de Freitas, Gabriella P. A.; Geraldo, Luiz Henrique M.; Faria, Bruna M.; Alves‐Leon, Soniza Vieira; de Souza, Jorge Marcondes; Moura‐Neto, Vivaldo; Pontes, Bruno; Romão, Luciana F.; Garcez, Patrícia P.
Abstract: Glioblastoma is the most common and malignant type of primary brain tumor. Previous studies have shown that alterations in centrosome amplification and its components are frequently found in treatment‐resistant tumors and may be associated with tumor progression. A centrosome protein essential for centrosome biogenesis is the centromere protein J (CENPJ), known to control the proliferation of neural progenitors and hepatocarcinoma cells, and also neuronal migration. However, it remains unknown the role of CENPJ in glioblastoma. Here we show that CENPJ is overexpressed in human glioblastoma cell lines in comparison to human astrocytes. Using bioinformatics analysis, we find that high Cenpj expression is associated with poor prognosis in glioma patients. Examining Cenpj loss of function in glioblastoma by siRNA transfection, we find impairments in cell proliferation and migration. Using a Cenpj mutant version with the deleted PN2‐3 or TCP domain, we found that a conserved PN2‐3 region is required for glioblastoma migration. Moreover, Cenpj downregulation modulates glioblastoma morphology resulting in microtubules stabilization and actin filaments depolymerization. Altogether, our findings indicate that CENPJ controls relevant aspects of glioblastoma progression and might be a target for therapeutic intervention and a biomarker for glioma malignancy. Abstract : Here we have examined the of Centromere protein J (CENPJ) expression and function in human glioblastoma cells. We found that CENPJ is overexpressed in glioblastoma cells. Through gain and loss of function of Cenpj, we show that it regulates morphology, cell proliferation and migration in glioblastoma. Our data suggest that CENPJ regulates glioblastoma migration through its PN2‐3 domain, known to destabilize microtubules. This research contributes to the understanding of relevant aspects of the glioblastoma biology, suggesting that CENPJ could be a potential target for therapeutic intervention.